Effects of Family-Work Conflict, Locus of Control, Self Confidence and Extraversion Personality on Employee Work Stress - ERDİLEK KARABAY, MELİSA (ELSEVIER SCIENCE BV, 2016)
Today employees are much more employed with various stressors in organizations. It is critical to determine these various stressors since work stress continues to influence organizational structure, significantly. This paper examines the interaction between family-work conflict, locus of control, self-confidence and extraversion personality on work-stressors. For this purpose, the data (N=413) was collected from the employees working in the production, food and municipal institutions, located in Istanbul. Empirical results indicate that family-work conflict affects work-overload, poor work environment and poor role congruence stressors positively and significantly. Internal locus of control is found to be affective on poor role congruence and poor organizational structure negatively whereas external locus of control is affective on poor organizational structure positively. Results indicate no significant effect of extraversion personality and self-confidence on stressors. (C) 2016 Published by Elsevier Ltd.
Keywords: Family-Work Conflict; Locus of Control; Personality; Work Stress; Self-Confidence; JOB-PERFORMANCE; OCCUPATIONAL STRESS; EXTERNAL CONTROL; METAANALYSIS; GENDER; MODEL; OUTCOMES; SUPPORT; HEALTH; REINFORCEMENT